Dual-Specificity Phosphatase 11 Is a Prognostic Biomarker of Intrahepatic Cholangiocarcinoma - Xu, Lin; Wang, Peng; Zhang, Wei; Li, Weiran; Liu, Tao; Che, Xu (Frontiers in Oncology, 2021)
Background Cholangiocarcinoma (CCA), including intrahepatic (iCCA), perihilar (pCCA) and distal (dCCA) CCA, is a highly aggressive malignancy originating from bile duct. The prognosis of CCA is very poor, and the biomarker study is unsatisfactory compared with other common cancers. Materials and methods In our study, we investigated the expression of dual-specificity phosphatase 11(DUSP11) in 8 pairs of iCCAs, pCCAs and dCCAs and their corresponding tumor-adjacent tissues, as well as their tumor-adjacent tissues with qPCR. Moreover, we investigated the expression of DUSP11 in 174 cases of CCAs with immunohistochemistry, including 74 iCCAs, 64 pCCAs and 36 dCCAs. We classified these patients into subsets with low and high expression of DUSP11, and evaluated the correlations between DUSP11 subsets and clinicopathological factors. With univariate and multivariate analyses, we assessed the correlation between DUSP11 and the overall survival (OS) rates in these CCA patients. Results In all the CCA subtypes, DUSP11 was elevated in CCAs compared with their paired adjacent tissues. In iCCA, pCCA and dCCA, the percentages of DUSP11 high expression were 44.59%, 53.85% and 55.56%, respectively. In iCCA, high DUSP11 expression was significantly associated with advanced T stage and poor prognosis. However, the prognostic value of DUSP11 in pCCA and dCCA was not significant. To decrease the statistical error caused by small samples size of dCCA cohort, we merged pCCA and dCCA into extracellular CCA (eCCA). In the 101 cases of eCCA, DUSP11 expression was also not significantly associated with the prognosis. Conclusions DUSP11 expression was associated with tumor infiltration and the OS rate in iCCA, but not in pCCA and dCCA. DUSP11 was an independent biomarker of iCCA indicating the poor prognosis. Our results suggested that high expression of DUSP11 was a post-operational risk factor, and detecting DUSP11 could guide the individual treatment for patients with CCA.